Climate Change Litigation to Protect the Right to Enjoy a Healthy Environment in Indonesia - Wartini, Sri; Dewi, Ayu Atika (Jurnal Media Hukum, 2026)
Climate change threatens Indonesia's constitutional right to a healthy environment. However, Indonesian courts have not developed a clear legal framework to handle climate harm as an independent basis of litigation. The aim of the study is to examine how climate litigation can be doctrinally structured within Indonesian law to protect the right to a healthy environment by analyzing constitutional provisions, human rights law, environmental legislation, administrative law, and international climate instruments. The research is a normative study employing conceptual, comparative, and statutory approaches, including the Human Rights Law, Law No. 32 of 2009, and administrative law mechanisms, to develop climate claims in the absence of a specific climate litigation statute. The article argues that climate litigation in Indonesia remains peripheral because courts usually frame climate-related disputes as ordinary environmental, forestry, or administrative cases. To address this problem, the article proposes a five-element doctrinal test for identifying climate litigation: climate-related harm, rights-based injury, identifiable legal duty, evidentiary causation, and climate-sensitive remedies. However, this requires clearer rules on causation, due diligence, scientific evidence, and remedies. The article recommends the adoption of judicial guidelines on climate litigation, statutory clarification of climate-related claims, and stronger integration of climate science into environmental adjudication.